Family Support and Anxiety Level of High Care Unit Patient - Ariesy, Chrysha Hayu; Mulyadi, Arif; Anam, Agus Khoirul (Health Access Journal, 2025)
Anxiety is prone to occur in patients in the intensive care unit. One factor that can reduce anxiety is family support. The purpose of this study was to determine the relationship between family support and the anxiety level of HCU patients at RSUD Dr. Soedono, East Java Province. This study used descriptive quantitative research. The population in this study were patients admitted to the HCU room at RSUD Dr. Soedono East Java Province in February 2024. The sample used was 30 patients who were determined using purposive sampling technique. The instrument used was a family support questionnaire modified from the Sitanggang questionnaire (2015), while the anxiety level was measured by HARS. Data were analyzed using the Spearman Rank test. The results showed that out of 30 HCU patients at RSUD Dr. Soedono East Java Province, more than half had high family support, while more than half had mild anxiety levels and no anxiety. There is no significant relationship between family support and anxiety level in HCU patients at RSUD dr.Soedono. The anxiety level of patients in the HCU is not only influenced by family support, there are other factors that can affect it such as length of treatment, experience of being treated, level of knowledge and treatment room environment